2013
DOI: 10.1159/000342561
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Central Fat Distribution Are Related to Lower Serum Osteocalcin Concentrations

Abstract: Background: The aim of this study was to evaluate the association of serum osteocalcin with the metabolic syndrome (MS) in men and premenopausal women. Methods: 14 middle-aged men and 44 premenopausal women were evaluated. MS was defined according to the International Diabetes Federation criteria. Anthropometric data were collected and serum osteocalcin, serum C-telopeptide (CTX), fasting plasma glucose (FPG) and lipid profile measured. Results: The mean age was 41.07 ± 8.4 years and did not differ between pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…19,20 In addition, a few studies suggesting an association between bone turnover markers and metabolic syndrome are available in the literature. 21,22 In particular, some authors have shown that male patients with metabolic syndrome had lower osteocalcin. 21 The majority of the studies demonstrated that most metabolic syndrome patients had reduced osteocalcin values, irrespective of sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 In addition, a few studies suggesting an association between bone turnover markers and metabolic syndrome are available in the literature. 21,22 In particular, some authors have shown that male patients with metabolic syndrome had lower osteocalcin. 21 The majority of the studies demonstrated that most metabolic syndrome patients had reduced osteocalcin values, irrespective of sex.…”
Section: Discussionmentioning
confidence: 99%
“…21 The majority of the studies demonstrated that most metabolic syndrome patients had reduced osteocalcin values, irrespective of sex. 20,22 One study showed that osteocalcin played a major role in the lipid and glucose metabolism, and patients suffering from obesity and impaired glucose tolerance had lower osteocalcin. 23 In another study, the authors found that osteocalcin was associated with BMI, WC, FBG, and systolic blood pressure and played a key role in the pathogenesis of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The association between bone resorption markers with the number of metabolic syndrome defining characteristics has not been well characterized and the results of previous studies are not consistent [29,34,35]. One study reported lower CTX in metabolic syndrome patients relative to healthy controls [35], while other studies did not observe such results, and no difference in CTX was found between metabolic syndrome patients with healthy controls [29,34]. In the present study, the bone resorption marker CTX was highest in participants with 3 metabolic syndrome defining characteristics.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, the mechanism underlying the association between fasting glucose and OC reported in the present study and other observational studies [31,33], requires further investigation. The association between bone resorption markers with the number of metabolic syndrome defining characteristics has not been well characterized and the results of previous studies are not consistent [29,34,35]. One study reported lower CTX in metabolic syndrome patients relative to healthy controls [35], while other studies did not observe such results, and no difference in CTX was found between metabolic syndrome patients with healthy controls [29,34].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation